2007
DOI: 10.1371/journal.pone.0001045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Plasmodium falciparum AMA1 Vaccine on Antibody Responses in Adult Malians

Abstract: BackgroundApical Membrane Antigen 1 (AMA1) of Plasmodium falciparum merozoites is a leading blood-stage malaria vaccine candidate. Protection of Aotus monkeys after vaccination with AMA1 correlates with antibody responses.Study Design/ResultsA randomized, controlled, double-blind phase 1 clinical trial was conducted in 54 healthy Malian adults living in an area of intense seasonal malaria transmission to assess the safety and immunogenicity of the AMA1-C1 malaria vaccine. AMA1-C1 contains an equal mixture of y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
59
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 28 publications
12
59
1
Order By: Relevance
“…We found that levels of antibodies to the three allelic recombinant proteins of the AMA1 ectodomain were highly correlated in this cohort of children. This is in keeping with previous studies of naturally acquired (14,47) and vaccineinduced (17) antibodies to AMA1. Of note, during acute infections and at convalescence, the correlation coefficients between antibodies to the three proteins had declined compared to those at the preseason time point, suggesting that antibodies to allele-specific epitopes had been induced by infection.…”
Section: Discussionsupporting
confidence: 92%
“…We found that levels of antibodies to the three allelic recombinant proteins of the AMA1 ectodomain were highly correlated in this cohort of children. This is in keeping with previous studies of naturally acquired (14,47) and vaccineinduced (17) antibodies to AMA1. Of note, during acute infections and at convalescence, the correlation coefficients between antibodies to the three proteins had declined compared to those at the preseason time point, suggesting that antibodies to allele-specific epitopes had been induced by infection.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of correlation in other studies may be explained partly by saturation of inhibitory activity in older study populations, with mean ages reaching 23.9 years (45) and 27.5 years (37) in some studies, versus 8.9 years in our study. This possibility is consistent with results from a phase 1 trial of the AMA1 vaccine in semi-immune Malian adults, which showed no increase in growth-inhibitory activity after vaccination despite a significant increase in antibody titers (16). Regarding the inverse correlation between age and growth-inhibitory activity, it is possible that polyclonal antibody responses to repeated infections over time generate antibodies to merozoite proteins that block invasion of RBC but also interfere with invasion-blocking antibodies (22,35).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, good functional properties of antibodies produced in response to a malaria vaccine candidate in naïve subjects may not translate to similar findings in semi-immune subjects. For example, Malian subjects who received a vaccine based on AMA-1 had good antibody responses, but the biologic activity of the total IgG did not change from that prevaccination, despite findings of high P. falciparum growth inhibition and antibody levels when the vaccine was tested in naïve subjects (10,20). Subsequent analysis suggested that this difference was due to the fact that other antimalarial antibodies in the Malian volunteers reduced the GIA effect of anti-AMA-1 antibodies (22).…”
Section: Discussionmentioning
confidence: 99%